An oxygen-rich vacancy CeO x @Cu catalysts, methods for their preparation and use in the reduction of nitrate

CN122649049APending Publication Date: 2026-08-28HARBIN NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610619000.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-07
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

[0008]本发明为了解决现有水中硝酸盐电化学还原过程中存在的亚硝酸盐(NO2-)向氨转化的动力学迟缓,以及活性氢(H)物种的供应不足的问题,提供一种富氧空位CeOx@Cu催化剂及其制备方法和在硝酸盐还原中的应用

Benefits of technology

本发明通过电沉积法将CeO2纳米颗粒均匀地负载在铜基底上,经过煅烧处理形成具有高密度氧空位的复合催化剂CeOx@Cu,氧空位介导的*H从CeOx向铜表面的溢流显著加速了硝酸盐还原动力学,同时抑制了副反应,显著提高了硝酸盐还原反应的催化活性和选择性。且CeOx的氧空位和Cu位点的协同作用促进了NO3-的高效还原,Ce位点促进了电子与质子的协同转移,降低了反应的能垒,提高了氨生成的选择性。在合适的电解液和电压条件下,CeOx@Cu复合催化材料表现出优异的氨生成性能(404.08μmol h-1cm-2)和高法拉第效率(FE达到94.6%),在短时间内实现水中NO3-的高效还原为氨,具有重要的环境和经济效益,尤其在水体污染治理领域具有广泛应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122649049A_ABST
    Figure CN122649049A_ABST
Patent Text Reader

Abstract

The application discloses an oxygen-enriched vacancy CeOx@Cu catalyst, a preparation method thereof and application of the catalyst in nitrate reduction, and belongs to the technical field of electrochemical catalytic materials and preparation thereof. The application solves the problems of slow kinetics of conversion of nitrite into ammonia and insufficient supply of active hydrogen species in the existing electrochemical reduction process of nitrate in water. In the application, CeO2 nanoparticles are uniformly loaded on a copper substrate by an electrodeposition method, and a composite catalyst CeOx@Cu with high-density oxygen vacancies is formed through calcination treatment, overflow of oxygen vacancy-mediated *H from CeOx to the copper surface significantly accelerates the reduction kinetics of nitrate, and side reactions are inhibited, thereby excellent ammonia generation performance (404.08 mu mol h ‑1 cm ‑2 ) and high Faraday efficiency (FE reaches 94.6%) are exhibited, and nitrate in wastewater can be effectively converted into ammonia, and electric energy can be recovered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an oxygen-rich vacancy CeO x @Cu catalysts, their preparation methods, and their applications in nitrate reduction, specifically involving a method utilizing oxygen-rich CeO₂ catalysts. x The method of using @Cu materials to efficiently reduce nitrates in water and simultaneously recover electrical energy belongs to the field of electrochemical catalytic materials and their preparation technology. Background Technology

[0002] Nitrate (NO3) - Nitrate is a common pollutant in water bodies. Excessive nitrate can lead to eutrophication and pose a potential threat to human health. Existing nitrate removal technologies, such as reverse osmosis, ion exchange, and biological denitrification, are effective in some applications, but these methods are often accompanied by problems such as high treatment costs, easy secondary pollution that is difficult to control, or long treatment cycles, making it difficult to achieve the full reuse of pure nitrate.

[0003] Ammonia (NH3), as an important basic chemical raw material, has broad application prospects in fertilizer production, hydrogen energy storage, and fuel cells. Directly reducing nitrate to ammonia not only efficiently removes nitrate from water but also enables resource recovery, possessing high environmental and economic value. Electrocatalytic nitrate reduction to ammonia (NO3RR) technology has emerged and rapidly become a research hotspot in the field of sustainable chemistry.

[0004] Electrochemical nitrate reduction reaction (NO3RR) has become an important nitrate removal technology due to its advantages such as simple operation, controllable process, and ability to be coupled with energy systems. However, existing electrocatalysts often suffer from problems such as poor catalytic activity, low selectivity, and poor durability, necessitating the development of new, highly efficient catalytic materials.

[0005] Electrochemical catalysts are the most crucial element determining the performance of NO3RR. Theoretically, ideal catalyst materials with high catalytic performance need to simultaneously meet multiple requirements, namely NO3... - The efficient adsorption and activation of nitrogen-containing intermediates, rapid hydrogenation of other nitrogen-containing intermediates, and effective suppression of the competing hydrogen evolution reaction (HER) are key factors in the NO3RR research field. Among numerous candidate materials, copper (Cu)-based catalysts have become a research focus due to their unique electronic configuration, suitable adsorption strength for nitrogen intermediates, and relatively low cost. In recent years, researchers have conducted extensive and fruitful explorations of copper-based catalysts, covering various material systems such as single-metal nanostructures, alloys, oxides, single-atom catalysts, and metal-organic frameworks. Through strategies such as electronic structure modulation, single / dual-atom engineering, tandem catalytic system design, and interface engineering, the nitrate conversion efficiency and ammonia selectivity of copper-based catalysts have been significantly improved.

[0006] However, despite the significant performance advantages of copper-based catalysts in NO3RR, their practical application still faces several key bottlenecks. The most prominent of these is the adhesion of copper surfaces to nitrite (NO2). - The slow kinetics of the conversion to ammonia and the insufficient supply of active hydrogen (H) species can both be traced back to the slow water dissociation kinetics on the copper surface. The energy barrier for water molecules to dissociate into H and OH on the copper surface is high, resulting in a H generation rate that is far from meeting the requirements of the nitrate hydrogenation step.

[0007] To address the aforementioned issues, it is essential to provide a novel electrocatalyst for the reduction of nitrates in water. Summary of the Invention

[0008] This invention aims to address the problem of nitrite (NO2) present in the existing electrochemical reduction process of nitrates in water. - To address the sluggish kinetics of nitrate conversion to ammonia and the problem of insufficient supply of active hydrogen (H) species, this paper provides an oxygen-vacancy-rich CeOx@Cu catalyst, its preparation method, and its application in nitrate reduction.

[0009] The technical solution of this invention: One objective of this invention is to provide an oxygen-rich CeO₂ vacancy-rich CeO₂. x A method for preparing Cu catalyst, comprising the following steps: Step (1) CeO2 is deposited on copper foam using electrodeposition technology; Step (2) involves calcining the sample deposited in step (1) under an inert gas atmosphere to obtain oxygen-rich CeO. x @Cu catalyst.

[0010] Further specifying, the electrolyte used for electrodeposition in step (1) is a cerium nitrate solution containing PEG.

[0011] Furthermore, the electrolyte is a 0.1-0.5M cerium nitrate solution with a small amount of PEG added.

[0012] Further specify that the copper foam is pretreated before electrodeposition in step (1).

[0013] To further specify, the preprocessing procedure is as follows: First, cut the foam copper into 2×2cm pieces. 2 The flakes were ultrasonically cleaned with 20-30 mL of acetone, deionized water and ethanol for 10-20 min each to remove surface organic matter and oxides. Then, the cleaned copper foam is immersed in 20-30 mL of 0.1-1 M HCl solution for 5-15 min to activate the surface and enhance the electrodeposition bonding force. It is then rinsed with deionized water and vacuum dried.

[0014] Further specifying, the current density in step (1) of the electrodeposition process is 20~40 mA·cm. - ².

[0015] Further specified, the calcination temperature in step (2) is 400~800℃ and the time is 1~4h.

[0016] Furthermore, the calcination temperature in step (2) is 600℃ and the time is 2h.

[0017] Further specifying, the inert gas atmosphere in step (2) is an argon atmosphere.

[0018] The second objective of this invention is to provide an oxygen-rich CeO₂ obtained by the above preparation method. x @Cu catalyst.

[0019] The third objective of this invention is to provide a CeO2-rich oxygen-vacancy site as described above. x The application of @Cu catalysts is specifically as catalysts for the electrochemical reduction reaction that reduces nitrates in water to ammonia.

[0020] The fourth objective of this invention is to provide a method for reducing nitrates, specifically using 0.1~1M Na2SO4 as the electrolyte and 0.01~0.2M nitrate solution as the reactant, to reduce NO3 through an electrochemical reduction reaction. - reduction.

[0021] Further specified, 0.5M Na2SO4 was used as the electrolyte and 0.1M nitrate solution was used as the reactant.

[0022] Further specifying, the operating voltage for the electrochemical reduction reaction process is -0.3 ~ -0.7V vs. RHE.

[0023] Furthermore, the operating voltage for the electrochemical reduction reaction process is -0.5V vs. RHE.

[0024] Beneficial effects: This invention uses an electrodeposition method to uniformly load CeO2 nanoparticles onto a copper substrate, followed by calcination to form a composite catalyst CeO2 with a high density of oxygen vacancies. x @Cu, oxygen vacancy-mediated *H from CeO x Overflow to the copper surface significantly accelerated nitrate reduction kinetics while suppressing side reactions, thus significantly improving the catalytic activity and selectivity of the nitrate reduction reaction. Furthermore, CeO₂...x The synergistic effect of oxygen vacancies and Cu sites promotes NO3. - The efficient reduction of CeO₂ is facilitated by the Ce sites promoting the cooperative transfer of electrons and protons, lowering the energy barrier of the reaction, and improving the selectivity of ammonia formation. Under suitable electrolyte and voltage conditions, CeO₂… x The Cu composite catalyst exhibits excellent ammonia generation performance (404.08 μmol h⁻¹). -1 cm -2 With high Faraday efficiency (FE reaching 94.6%), NO3 in water can be reduced in a short time. - The efficient reduction of ammonia to ammonia has significant environmental and economic benefits, and it has broad application prospects, especially in the field of water pollution control.

[0025] CeO treated by calcination x The Cu composite material exhibited excellent stability and catalytic activity during prolonged reactions, maintaining good catalytic performance through multiple reaction cycles without significant loss of activity or structural degradation, indicating its extremely strong long-term stability. Furthermore, under different pH conditions, CeO₂… x The @Cu catalyst remains stable and highly adaptable, effectively carrying out nitrate reduction reactions in neutral, acidic, or alkaline environments.

[0026] Further use of its assembled Zn-NO3 - The battery exhibited excellent stability and high power density, achieving energy recovery and highlighting CeO's performance. x The potential of @Cu cathodes in practical energy conversion.

[0027] In summary, CeO x @Cu can not only efficiently reduce nitrates to ammonia in electrochemical reactions, but also recover electrical energy in the process, realizing simultaneous denitrification of wastewater and recovery of electrical energy. It can be widely used in the treatment of agricultural wastewater, industrial wastewater containing nitrates and groundwater. Attached Figure Description

[0028] Figure 1 To prepare CeO x @Cu flowchart; Figure 2 CeO prepared in Examples 1-3 x SEM image of @Cu; Figure 3 CeO prepared for Examples 1, 4 and 5 x SEM image of @Cu; Figure 4 (a) is a SEM image of copper foam, and (b) is a CeO2 image prepared in Example 1. xSEM image of @Cu; Figure 5 CeO prepared in Example 1 x TEM images of @Cu (at different resolutions); Figure 6 CeO prepared in Example 1 x @Cu's EDS element mapping; Figure 7 CeO prepared in Example 1 x XRD comparison chart of Cu with Cu and CeO2; Figure 8 CeO prepared in Example 1 x EPR spectra of @Cu and CeO2@Cu; Figure 9 CeO prepared in Example 1 x Ce 3d XPS spectra of @Cu; Figure 10 Ce 3d XPS spectrum of CeO2@Cu prepared in Example 1; Figure 11 CeO prepared in Example 1 x O 1s XPS spectrum of @Cu; Figure 12 The O 1s XPS spectrum of CeO2@Cu prepared in Example 1; Figure 13 The Cu 2p XPS spectrum of CeO2@Cu prepared in Example 1; Figure 14 CeO prepared in Example 1 x Cu 2p XPS spectrum of @Cu; Figure 15 CeO prepared in Example 1 x Free energy curves of @Cu, CeO2@Cu, and NO3RR of Cu Figure 16 CeO prepared in Example 1 x Comparison of the free energy changes of @Cu, CeO2@Cu, and Cu for HER and NO3RR; Figure 17 CeO prepared in Example 1 x LSV curve of @Cu; Figure 18 CeO prepared in Example 1 x @Cu Ammonia yield and FE variation at different potentials; Figure 19 CeO prepared in Example 1 x @Cu comparison of FE of main product and other byproducts at different potentials; Figure 20 CeO prepared in Example 1 x The catalytic stability test results of @Cu are shown in (a) for cyclic stability and (b) for long-term stability. Figure 21 CeO prepared in Example 1 x @Cu as cathode assembly of Zn-NO3 - Schematic diagram and actual image of the battery device; Figure 22 CeO prepared in Example 1 x @Cu as cathode in the assembly of Zn-NO3 - The constant discharge curve of the battery (neutral electrolyte). Figure 23 CeO prepared in Example 1 x @Cu as cathode in the assembly of Zn-NO3 - The discharge polarization curve of the battery and the corresponding power density (alkaline electrolyte). Figure 24 In the image, (a) is the concentration-absorbance curve of ammonia, and (b) is the standard curve of ammonia. Figure 25 In the image, (a) is the concentration-absorbance curve of nitrite, and (b) is the standard curve of nitrite. Figure 26 In the figure, (a) is the concentration-absorbance curve of hydrazine, and (b) is the standard curve of hydrazine. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0030] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. The materials, reagents, methods, and instruments used, unless otherwise specified, are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0031] Example 1 like Figure 1 As shown, the oxygen-vacancy-rich CeO prepared by this invention x The @Cu process is as follows: (a) Preparation of CeO x @Cu catalyst Step (1): Pretreatment of copper foam substrate 1) Cutting and cleaning: Cut the foamed copper into 2×2cm pieces. 2The flakes were ultrasonically cleaned sequentially with acetone, deionized water, and ethanol (30 mL each) for 10 min each to remove surface organic matter and oxides.

[0032] 2) Acid activation: Immerse the cleaned copper foam from step 1) in 30 mL of 0.2 M dilute HCl solution for 10 min to activate the surface and enhance the electrodeposition bonding force. Then rinse with deionized water and perform vacuum drying.

[0033] Step (2): Preparation of CeO2@Cu The 2×2cm after step (1) 2 Using a foamed copper electrode as the working electrode, at a current density of 30 mA / cm² -2 The electrolyte was a 0.1M cerium nitrate solution, with 0.0005g of polyethylene glycol (PEG) added as an additive to regulate the surface structure of the material and promote Ce24-245 electrolysis. 3+ To ensure sufficient dispersion and obtain uniformly dispersed CeO2@Cu, the electrodeposition time was controlled to be 60 min to obtain CeO2@Cu.

[0034] Step (3): CeO with oxygen-rich vacancies x Preparation of Cu The CeO2@Cu obtained in step (2) was calcined under an argon atmosphere at a temperature of 600℃ for 2 hours to obtain oxygen-rich CeO2@Cu. x @Cu.

[0035] Example 2 The difference between this embodiment and embodiment 1 is that the electrodeposition time in step (2) is controlled to be 30 min, while the remaining process steps and parameter settings are the same as in embodiment 1.

[0036] Example 3 The difference between this embodiment and embodiment 1 is that the electrodeposition time in step (2) is controlled to be 90 min, while the remaining process steps and parameter settings are the same as in embodiment 1.

[0037] Example 4 The difference between this embodiment and embodiment 1 is that the current density in step (2) is 20 mA cm⁻¹. -2 The remaining process steps and parameter settings are the same as in Example 1.

[0038] Example 5 The difference between this embodiment and embodiment 1 is that the current density in step (2) is 40 mA cm⁻¹. -2 The remaining process steps and parameter settings are the same as in Example 1.

[0039] Example of effect CeO with oxygen-rich vacancies obtained x The microstructure and properties of Cu were characterized, and the results are as follows: (1) CeO2 with oxygen-rich vacancies prepared in Examples 1-3 x Microscopic morphology characterization of @Cu was performed, and the results are as follows: Figure 2 As shown, the effect of different electrodeposition times on the catalyst morphology was investigated. SEM images of the materials with electrodeposition times of 30 min, 60 min, and 90 min are shown in the figure. Figure 2 In sections a, b, and c, too short a deposition time leads to uneven crystal growth, while too long a time results in crystal aggregation and increased particle size. Therefore, electrolysis for 60 minutes was ultimately chosen as the optimal CeO2@Cu synthesis scheme, and CeO2 was prepared by calcination. x @Cu.

[0040] (2) CeO2 with oxygen-rich vacancies prepared in Examples 1, 4 and 5 x @Cu was used for microscopic morphology characterization, by Figure 3 It is known that, in order to determine the optimal preparation conditions, at 20 mA cm⁻¹ -2 30 mA cm -2 and 40 mA cm -2 CeO2@Cu samples were prepared at different current densities, and the SEM images correspond to the following: Figure 3 In sections a, b, and c, at lower current densities, the limited number of active sites on the electrode surface results in fewer and larger particles. Conversely, higher current densities provide a stronger electrochemical driving force, promoting the rapid generation of numerous fine nuclei and accelerating growth kinetics, leading to particle aggregation and a coarser surface morphology. Therefore, a 30 mA cm⁻¹ electrode was determined to be suitable. -2 The current density is optimal.

[0041] (3) Scanning electron microscopy (SEM) was used to examine the copper foam and the CeO2 prepared in Example 1. x The surface morphology of Cu was characterized. The results are as follows: Figure 4 As shown in the figure, CeO x @Uniformly loaded CeO on Cu surface x Furthermore, the Cu substrate maintains a good foam structure, which is beneficial to enhancing the catalytic activity and stability of the material.

[0042] (4) The CeO2 prepared in Example 1 was examined using transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM). x @Cu loaded CeO x The uniformity performance was further verified, and the results are as follows: Figure 5 As shown, by Figure 5 It can be seen that CeO xA tight bond was formed between the CeO and the copper substrate, and HRTEM(b) revealed clear phase boundaries, indicating the formation of a strong interfacial network. A lattice spacing of 0.19 nm was observed, which is attributed to the oxygen-vacancy-rich CeO. x Characteristic lattice expansion or distortion.

[0043] (5) Figure 6 CeO prepared in Example 1 x The EDS elemental mapping of @Cu, where Cu (green), Ce (blue), and O (red), shows that Cu, Ce, and O are highly uniformly distributed in the catalyst structure, verifying the CeO group. x Successful construction of the @Cu heterostructure.

[0044] (6) CeO prepared in Example 1 x The crystal structure of @Cu was analyzed by XRD, such as Figure 7 As shown, the XRD pattern reveals the characteristic diffraction peaks of metallic Cu and fluorite CeO2, verifying the successful formation of the heterostructure. Specifically, the significant peak at approximately 28.5° corresponds to the (111) crystal plane of CeO2. A magnified view of the (111) diffraction region shows that the diffraction peaks of CeOx@Cu are significantly shifted to a lower 2θ angle compared to the original CeO2. This shift is a classic characteristic of lattice expansion within the ceria framework. This lattice distortion is primarily attributed to Ce... 4+ (Ionic radius ≈ 0.97 Å) Partially reduced to the larger Ce 3+ The process (ionic radius ≈ 1.14 Å) requires the formation of oxygen vacancies (Ov) to maintain charge neutrality. This demonstrates the successful construction of a defect-rich interface in the CeOx@Cu catalyst.

[0045] (7) Figure 8 CeO prepared in Example 1 x The EPR spectrum of @Cu shows a distinct signal at g=2.03, which is a characteristic fingerprint of unpaired electrons in oxygen vacancy sites.

[0046] (8) The valence state of Ce was investigated using XPS Ce 3d spectra, and the CeO valence state was also investigated. x Deconvolution of the spectra of @Cu and CeO2@Cu samples yielded ten distinct peaks, as shown below. Figure 9 and 10 As shown in the figure, the multiple peaks at 882.4, 889.0, 898.4, 901.1, 907.7, and 916.7 eV are attributed to Ce. 4+ The species, while the peaks at 880.5, 885.2, 898.8, and 903.8 eV are attributed to Ce. 3+species. The quantitative integration results show that CeO x @Cu has a Ce 3+ concentration significantly higher than that of CeO2@Cu. The enrichment of Ce 3+ is closely related to the increase in oxygen vacancies, and this finding is further verified by O 1s XPS analysis, as shown in Figure 11 and Figure 12 . Compared with CeO2@Cu, the peak intensity related to oxygen vacancies (Ov) in CeO x @Cu is significantly enhanced. In addition, as can be seen from the Cu 2p XPS spectra shown in Figure 13 and 14 , the binding energy characteristics at 932.6 eV (2p3 / 2) and 952.4 eV (2p1 / 2) indicate the existence of metallic Cu. The change in binding energy is small, indicating that the electronic structure of the copper foam barely changes after the deposition of CeO2 clusters, and the enhancement of catalytic performance mainly originates from the CeO x and Cu interface.

[0047] (9) Application of CeO x @Cu Catalyst The CeO x @Cu prepared in Example 1 was subjected to LSV (Linear Sweep Voltammetry) tests in 0.5 M Na2SO4 solution and 0.5 M Na2SO4 + 0.1 M NaNO3 solution. The results show that compared with the hydrogen evolution reaction (HER), the CeO x @Cu material has better NO3RR activity, indicating the superior performance of the material in nitrate reduction, as shown in Figures 15-17 .

[0048] Through gradient voltage tests (-0.3~-0.7 V vs. RHE), the optimal ammonia production potential was found, and the corresponding Faradaic efficiency (FE) was measured. The test results are shown in Figure 18 , at the optimal working voltage (-0.5 V vs. RHE), the system can produce ammonia (NH3) at a rate of 404.08 μmol h -1 cm -2 . At -0.5 V vs. RHE, the Faradaic efficiency (FE) reaches 94.6%, indicating the high efficiency and high selectivity of CeO x @Cu during nitrate reduction.

[0049] The production amounts of ammonia and its by-products at different potentials were characterized, and the specific process is as follows: 1) NH3 Concentration: The concentration of NH3 in the electrolyte was determined by the indophenol blue method. The specific procedure is as follows: Take 2 mL of NH3 standard solution electrolyte diluted to the appropriate ratio, mix it with the colorimetric solution (A: 2.5 g salicylic acid + 2.845 g sodium citrate + 2 g NaOH; B: 3.5 mL NaClO solution dissolved in 100 mL water; C: 0.05605 g C5FeH6Na2O), and let it stand in the dark for 20 min. Measure the absorbance at 625 nm using a UV-Vis spectrophotometer. The results are as follows: Figure 24 As shown in Figure a. Based on the standard calibration curve (y=0.63943x+0.1262, R... 2 The concentration of NH3 was calculated using the formula (=0.999), and the result is as follows: Figure 24 As shown in b.

[0050] 2) Byproduct NO2 - Concentration: Quantified using the Griess reagent method. The colorimetric solution was prepared as follows: 2 mL of N₂H₄ standard solution diluted to the appropriate concentration was used to establish a calibration curve. 1 mL of H₃PO₄, 0.02 g of N-(1-naphthyl)ethylenediamine dihydrochloride, and 0.5 g of sulfanilamide were dissolved in 10 mL of deionized water. 1 mL of the diluted electrolyte was mixed with the colorimetric solution, and after standing at room temperature for 20 min, the absorbance was measured at 440 nm. The NO₂ concentration was determined by comparison with the standard solution. - Concentration, results as follows Figure 25 As shown.

[0051] 3) Concentration of byproduct N2H4: The Watt-Chris method was used for monitoring. 2 mL of N2H4 standard solution was diluted to the appropriate concentration to establish a calibration curve. The colorimetric reagent consisted of p-dimethylaminobenzaldehyde, ethanol, and concentrated hydrochloric acid. After dilution, pH adjustment, and color development for 20 min, the UV-Vis absorption spectrum in the range of 100–700 nm was recorded. The maximum absorption wavelength was approximately 455 nm. Based on this, the N2H4 concentration could be quantitatively determined. The results are as follows: Figure 25 As shown.

[0052] Figure 19 The graph shows the FE of the main product and other byproducts at different potentials. As can be seen from the graph, the amount of ammonia produced gradually increases with the increase of voltage, and the Faraday efficiency also shows a significant improvement.

[0053] Cyclic stability testing was conducted, with a long-term stability test duration of 36 hours and 10 cycles. The test results are as follows: Figure 20 As shown, by Figure 20 It can be seen that CeO x @Cu maintained high catalytic activity during long-term use, and its catalytic performance did not significantly decline, indicating that the catalyst has good long-term stability.

[0054] This is due to oxygen-rich vacancies in CeO. x CeO in Cu composites x Synergistic effect with Cu sites promotes NO3 - Highly efficient reduction of CeO. x The high density of adsorption sites provided by oxygen vacancies enhances the activation process of H2O. The generated active *H migrates to adjacent Cu sites via a spillover mechanism to participate in intermediate reduction. This spatial separation of water splitting and nitrate reduction sites effectively inhibits the competitive hydrogen evolution reaction, significantly accelerates the overall NO3RR kinetics, and promotes NO3 reduction during the reduction process. - The conversion to ammonia. This involves oxygen-rich vacancies in CeO₂. x Partially, the high-density oxygen vacancies enhance the adsorption capacity for H2O, creating a hydrogen pump effect and effectively lowering the initial activation energy of its reduction reaction. These oxygen vacancies provide a continuous hydrogen source and channel for the overflow of active *H, accelerating the consumption of rate-determining intermediates, thereby promoting NO3-. - The reduction of NO3. Cu sites in CeOx@Cu composites promote electron transfer and NO3 reduction. - The gradual reduction of nitrates promotes the formation of intermediates (such as *NO2, *NO, *NH2, etc.) during the reduction process, further increasing the rate of nitrate reduction. Subsequently, the synergistic effect between CeOx and Cu promotes the multi-step reduction of nitrates. In particular, under the influence of oxygen-rich vacancies, the catalytic activity and selectivity of the material are significantly improved, and the formation of by-products is reduced.

[0055] Further, such as Figure 21 As shown, CeO x @Cu as the cathode, zinc foil as the anode, assembling Zn-NO3 - The battery has a neutral electrolyte of 0.5M Na₂SO₄ + 0.1M KNO₃ solution, pH = 7, and an open-circuit voltage (OCV) of 1.054V vs. Zn. 2+ / Zn is sufficient to drive low-power devices such as custom LED circuits. And the assembled Zn-NO3 - Battery constant discharge curve as follows Figure 22 As shown, the battery exhibits excellent stability and high power density.

[0056] Under alkaline conditions, i.e., with an alkaline electrolyte of 0.1M NO3... - + 1M KOH, pH = 14, open-circuit voltage (OCV) increases to 1.125V vs. Zn. 2+ / Zn, this is mainly due to the inhibition of the cathode hydrogen evolution reaction (HER). And the assembled Zn-NO3 - Battery discharge polarization curve and corresponding power density are as follows: Figure 23 As shown in the figure, 15mA cm -2 Peak power density reaches 5.85 mW / cm². -2 .

[0057] Further testing of the battery capacity showed that under neutral conditions, the actual capacity was close to the theoretical capacity, while under alkaline conditions, due to the OH-... - With increasing concentration, the reversibility of the zinc anode decreases, affecting the cycle stability of the battery. However, the battery exhibits over 90% ammonia selectivity and nitrate removal efficiency under both neutral and alkaline conditions. Continuous discharge experiments show that the battery performs well at 15 mA cm⁻¹. -2 Under these conditions, it exhibits excellent long-term stability. Therefore, the Zn-NO3 of the present invention... - Battery system through CeO x The application of @Cu catalysts has enabled efficient nitrate removal and stable power output, providing a sustainable solution for environmental pollution control and energy recovery.

[0058] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone skilled in the art can make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be determined by the claims.

Claims

1. An oxygen-rich CeO3- vacancy-rich CeO3 x The method for preparing Cu catalyst is characterized by, include: Step (1) CeO2 is deposited on copper foam using electrodeposition technology; Step (2) involves calcining the sample deposited in step (1) under an inert gas atmosphere to obtain oxygen-rich CeO. x @Cu catalyst.

2. The preparation method according to claim 1, characterized in that, In step (1), the electrolyte used for electrodeposition is a cerium nitrate solution containing PEG.

3. The preparation method according to claim 1, characterized in that, The current density in step (1) of the electrodeposition process is 20~40 mA·cm. - ².

4. The preparation method according to claim 1, characterized in that, In step (2), the calcination temperature is 400~800℃ and the time is 1~4h.

5. The preparation method according to claim 1, characterized in that, In step (2), the inert gas atmosphere is an argon atmosphere.

6. An oxygen-enriched CeOx@Cu catalyst obtained by the preparation method according to any one of claims 1 to 5.

7. An oxygen-enriched CeO3 solution as described in claim 6 x The application of Cu catalyst is characterized by, It is used as a catalyst in the electrochemical reduction reaction to reduce nitrates in water to ammonia.

8. A method for reducing nitrates, characterized in that, Using 0.1–1 M Na₂SO₄ as the electrolyte and 0.01–0.2 M nitrate solution as the reactant, NO₃⁻ is reduced via an electrochemical reduction reaction. - reduction.

9. The reduction method according to claim 8, characterized in that, The operating voltage for the electrochemical reduction reaction process is -0.3 ~ -0.7V vs. RHE.

10. The reduction method according to claim 9, characterized in that, The operating voltage for the electrochemical reduction reaction process is -0.5V vs. RHE.